Instructor’s Leadership Style Improves Student Learning Motivation at Akademi Penerbang Indonesia Banyuwangi - Satria Laksmana Putra; Setyo Haryadi Suranto Putro; Dede Ardian; Dimas Hari Cahyo (Technium Social Sciences Journal, 2024)
The study "Instructor’s Leadership Style Improves Student Learning Motivation at Akademi Penerbang Indonesia Banyuwangi" examines how instructor leadership influences student motivation at API Banyuwangi. Learning motivation is key to academic success, and both intrinsic and extrinsic factors affect it. This study highlights the significant role instructors play in shaping student motivation through their leadership style. Using a quantitative approach, the researchers collected data from students and flight instructors via surveys. Two questionnaires were used: one to measure leadership style and another to assess student motivation. The sample was selected using stratified random sampling to ensure broad representation. The data was analyzed using SmartPLS 3, a tool that supports structural equation modeling and bootstrapping. Key findings show that specific leadership behaviors, such as giving clear instructions, offering constructive feedback, and using varied teaching methods, significantly enhance student motivation. Students are more motivated when instructors are seen as fair and engaging, which positively impacts their learning commitment. The analysis demonstrated that 74.2% of the variance in student motivation could be attributed to instructor leadership style, highlighting its importance. The study concludes that effective instructor leadership is crucial in boosting student motivation at API Banyuwangi. By fostering a supportive and engaging learning environment, instructors can enhance academic outcomes. The research emphasizes the importance of continuous professional development and innovative teaching practices to keep students motivated and committed to their studies.